2003
DOI: 10.4049/jimmunol.170.9.4441
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrazole Derivative, YM-58483, Potently Inhibits Store-Operated Sustained Ca2+ Influx and IL-2 Production in T Lymphocytes

Abstract: In nonexcitable cells, Ca2+ entry is mediated predominantly through the store depletion-dependent Ca2+ channels called store-operated Ca2+ (SOC) or Ca2+ release-activated Ca2+ channels. YM-58483, a pyrazole derivative, inhibited an anti-CD3 mAb-induced sustained Ca2+ influx in acute T cell leukemia, Jurkat cells. But it did not affect an anti-CD3 mAb-induced transient intracellular Ca2+ increase in Ca2+-free medium, nor anti-CD3 mAb-induced phosphorylation of phospholipase Cγ1. It was suggested that YM-58483 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(198 citation statements)
references
References 30 publications
7
187
4
Order By: Relevance
“…This contradicts with the report that Pyr2 failed to alter membrane potential in Jurkat cells (25). In addition, when external Na ϩ ions were completely replaced by the nonpermeant organic cation N-methyl-Dglucamine, Sr 2ϩ influx activated by CCh still showed an intact sensitivity to Pyr2, leading to an idea that the action of Pyr2 to block TRPC3 channels is independent of the membranedepolarizing action of TRPM4 (27).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This contradicts with the report that Pyr2 failed to alter membrane potential in Jurkat cells (25). In addition, when external Na ϩ ions were completely replaced by the nonpermeant organic cation N-methyl-Dglucamine, Sr 2ϩ influx activated by CCh still showed an intact sensitivity to Pyr2, leading to an idea that the action of Pyr2 to block TRPC3 channels is independent of the membranedepolarizing action of TRPM4 (27).…”
Section: Discussioncontrasting
confidence: 53%
“…Several reports have suggested that BTP2 (Pyr2) is a potent inhibitor for both Ca 2ϩ release-activated Ca 2ϩ (CRAC) channels and TRPC channels and for NFAT-driven IL-2 production (25)(26)(27). Structure-function relationships in BTPs proposed that 4Ј-[3,5-bis(trifluoromethyl)pyrazol-1-yl]-carboxanilide moiety is useful for discovering potent inhibitors for CRAC channels (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, CRAC channels have been proposed as potential target in the therapeutic management of autoimmune and inflammatory disorders. Recent in vitro studies showed that pyrazole derivatives potently inhibit Ca 2ϩ influx through CRAC, thus counteracting T cell activation and NFAT-driven IL-2 production by activated T cells (21,22).…”
Section: D4mentioning
confidence: 99%
“…Specific www.nature.com/aps Zhang HZ et al Acta Pharmacologica Sinica npg CRAC channel inhibitors may be developed into new safe and potent immune suppressors, which would benefit patients with these diseases. Thus far, a variety of small molecules blocking the CRAC channel have been identified, such as the imidazole derivative, SKF96365 (IC 50 of approximately 4 μmol/L) [15,16] , 2-APB [at low concentrations of 1-5 μmol/L, 2-APB potentiates CRAC currents, whereas high concentrations (>10 μmol/L) cause a transient enhancement of CRAC currents followed by a complete block in S2 for mammalian cells] [17,18] , YM58483 (IC 50 of approximately 150 nmol/L after 24 h of preincubation; IC 50 of approximately 10 μmol/L immediately after addi tion) [19,20] , and Synta 66 (IC 50 of approximately 3 μmol/L) [21] ( Figure 1); however, these compounds are not specific because they interfere with a variety of other transport processes. The only specific CRAC channel inhibitor tested in human is CM2489 [22] , the structure of which has not yet been disclosed.…”
Section: Introductionmentioning
confidence: 99%